Associations between meteorological factors and pregnancy complications during different pregnancy trimesters: a multicenter retrospective study in eastern China - Tao Chen; Jie Cai; Da He; Hui Zhu; Xiang Chen; Yuqiong Li; Wen Ye; Bingqi Li; Qinyan Xu; Lindan Ji; Jin Xu (PeerJ, 2025)
Background Previous studies have demonstrated the effects of ambient temperature on the risk of pregnancy complications. However, the associations between multiple meteorological factors and pregnancy complications have rarely been studied. Methods We carried out a retrospective study on the impacts of meteorological factors on pregnancy complications in different trimesters in Ningbo, China, from 2013–2023. Daily meteorological factors data were obtained from the National Aeronautics and Space Administration (NASA). Moreover, a meteorological factor score (MFS) was calculated. Logistic regression models were applied to assess the effects of individual meteorological factors and MFS on pregnancy complications during different trimesters. Distributed lag nonlinear models were used to explore the sensitive time windows of extreme meteorological factors in different weeks of gestation. The interaction effects of extreme meteorological factors were assessed. Results A total of 92,332 participants were included in the study, with diagnoses as follows: gestational diabetes mellitus (GDM) in 17,814 participants (19.29%), gestational hypertension (GH) in 3,860 participants (4.18%), preeclampsia (PE) in 3,101 participants (3.36%), and hypothyroidism in 17,418 participants (18.86%). Participants in the highest MFS quintile during the first trimester had greater risks of GDM (aOR = 1.186, 95% CI [1.079–1.304]), GH (aOR = 1.596, 95% CI [1.323–1.925]), PE (aOR = 1.347, 95% CI [1.094–1.658]) and hypothyroidism (aOR = 1.257, 95% CI [1.141–1.385]) compared to the lowest quintile. Extreme meteorological exposures influenced complications within distinct windows: risks of GDM, GH, and PE concentrated in mid-pregnancy (3rd–5th months), while hypothyroidism showed first-trimester vulnerability. Interactions between meteorological factors collectively influenced the risk of hypothyroidism. Conclusions Our findings demonstrated that elevated temperature, increased precipitation, prolonged sunshine duration, and reduced surface pressure were critical risk factors for pregnancy complications. Targeted protective measures should be taken to reduce the risk of pregnancy complications.